Impact of Wages, Unemployment Rates, and Inflation on Labor Forece Participation - Ramadhani, Novira Eka; Karjati, Pratiwi Dwi (Jurnal Ekonomika : INDEPENDEN, 2025)
Employment is a crucial element in supporting a country's economic progress. This study aims to evaluate the impact of several macroeconomic indicators, namely minimum wages, unemployment, and inflation, on the labor force participation rate in six ASEAN member countries (ASEAN-6). This study uses a quantitative approach through panel data regression analysis with a random effect model. The findings of the study indicate that minimum wages have no effect on labor force participation, while unemployment and inflation rates have been shown to have a significant effect.